EXCEL ЭЛЕКТРОН КЕСТЕ ПРОГРАММАСЫНДА СЫЗЫҚЛЫ ПРОГРАММАЛАСТЫРЫЎ МӘСЕЛЕЛЕРИН СИМПЛЕКС УСЫЛЫ МЕНЕН ШЕШИЎ - Жалелов, Р.М.; Жалелов, K.М. (SCIENCE and SOCIETY, 2020)
The article deals with the statement of a problem of linear programming and its decision with the help of a simplex method. Here it is presented the sequence of the decision of a problem and results of calculations by means of program Excel.
Keywords: linear programming; simplex method; criterion function; the basic solution; basis; the optimum solution